Analisis Kemampuan Pemahaman Matematis Dengan Memanfaatkan Aplikasi Microsoft Teaams di Masa Pandemi Covid-19 - Laras Yulia; Maman Fathurrohman; Hepsi Nindiasari (Universitas Sultan Ageng Tirtayasa, 2021)
This study aimed to analyze and describe the seventh-grade junior high school students’ mathematical understanding ability on comparison material using Microsoft Teams application during the covid-19 pandemic. This study employed a qualitative descriptive. The sampling technique used was the purposive random sampling technique. Subjects of this research were 35 students of class VII F SMP Negeri 1 Cilegon. The results show that student’s mathematical understanding using Microsoft Teams application during the covid-19 pandemic ability is 68% at high level category and 32% at low level category. Microsoft Teams is highly recommended for online learning in time of this pandemic.